Pembuatan Surfaktan Di Alkil Karbohidrat dari Alga - Mahreni M (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Surfactant (surface active agent) has capability todecrease surface tension, interfacial tension and increase emulsion stability. Most of surfactant used in industry is produced from petroleum based. As petroleumis limited resources, the development of surfactant using renewable resources is more needed. Macro algae containrich of polysaccharides such as agarose, carrageenans, and alginates. Some research has been done to study the production of new bio surfactant through the reaction of these polysaccharides with alcohol and lipid acid to promote high hydrophobic and hydrophilic site. Thispaper compared the production and the characterization of new biosurfactant, di-alkyl carbohydrate, from various macro algae such as brown algae (Sargasum sp), red algae (Euchema cottonii),and green algae. The main process was the extraction of polysaccharides at temperature of 80˚C, followed by esterification. Result indicated that all surfactant produced could create oil inwater emulsion system. Interfacial Tension tests were found in therange of 0,8 to 3,96 dyne/cm with surfactant concentration 1-2,5% respectively. Fourier Transfer Infrared analysis has indicated that the product contain ester bond which lead to surfactant formation.